Pyogenic granuloma-a 19 months follow up case report (Update Dental College Journal, 2015)
Pyogenic granuloma is one of the inflammatory hyperplasia seen in the oral cavity. This term is a misnomer because the lesion is unrelated to infection and in reality arises in response to various stimuli such as low- grade local irritation, traumatic injury or hormonal factors. Clinically, oral pyogenic granuloma is a smooth or lobulated exophytic lesion manifesting as small, red erythematous papules on a pedunculated or sometimes sessile base, which is usually hemorrhagic. The surface ranges from pink to red to purple, depending on the age of the lesion. Because of the high frequency of pyogenic granuloma in the oral cavity, especially during pregnancy, and necessity for proper diagnosis and treatment, a complete information and investigations about this lesion, in addition its treatment is presented. The study emphasizes the clinical follow-up after the treatment of patients that present pyogenic granuloma. Follow-up over 19 months of surgical procedures demonstrated the maintenance of a periodontal health decreases the chances of recurrence.Update Dent. Coll. j: 2015; 5 (1): 26-29